Professional Preparation of Teachers of Students With Visual Impairments and Orientation and Mobility Specialists Regarding Physical Activity, Physical Education, and Sport. (March 2022) - Sladewski, Jennifer; Lieberman, Lauren J.; Haibach-Beach, Pamela; Conroy, Paula
Introduction: This aim of this online study was to determine what teachers of students with visual impairments (TVIs) and orientation and mobility (O&M) specialists learned and experienced in their professional preparation programs regarding physical education, physical activity, and sport for students with visual impairments.Methods: In 2019, an initial questionnaire was sent to specialists in the field for validation. In 2020, 68 TVIs and O&M specialists participated in an online research study consisting of validated multiple choice, Likert scales, and short responses. This study was created through and accessed by participants on the website of Qualtrics, a survey tool.Results: Sixty percent of the participants did not feel that their professional preparation program provided an adequate amount of time discussing accommodations for students with visual impairments in physical education and physical activity. Eighty percent of participants learned very little or nothing at all in their courses related to physical activity, physical education, and sport; and 79% learned very little or nothing at all in their practicum experiences. Seventy-two percent of participants indicated that they wished that they had learned more about physical activity, physical education, and sport.Discussion: The findings demonstrate that TVIs and O&M specialists are not prepared to assist physical education teachers in making physical activity, physical education, and sport accessible to students with visual impairments.Implications for Practitioners: The professional preparation programs of TVIs and O&M specialists can include more information on making physical activity, physical education, and sport accessible to students with visual impairments.